Game Ranch management - G. de Graaff (Koedoe: African Protected Area Conservation and Science, 1989)
This book is the result of six years' intensive research and brainstorming by a group of South Africans under the editorship of J. du P. Bothma, the incumbent of the Eugene Marais Chair of Wildlife Management at the University of Pretoria. The group, comprising professional botanists and zoologists, veterinarians and wildlife managers, emphasises the fact that game (in all its characteristics and attributes) is unquestionably a natural asset in many parts of southern Africa